2020
DOI: 10.1177/1545968320943573
|View full text |Cite
|
Sign up to set email alerts
|

Greater Occipital Nerve Stimulation Boosts Associative Memory in Older Individuals: A Randomized Trial

Abstract: Transcutaneous electrical stimulation (tES) is a new approach that aims to stimulate the brain. Recently, we have developed tES approaches to enhance plasticity that modulate cortical activity via the greater occipital nerve (ON) in a “bottom-up” way. Thirty subjects between the ages of 55 and 70 years were enrolled and tested using a double-blind, sham-controlled, and randomized design. Half of the participants received active stimulation, while the other half received sham stimulation. Our results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The present study provides a replication of ON-tDCS having no direct effect on learning, but does have an effect on memory being observed on Day 7, further depicting active ON-tDCS' viability for upregulating the LC-NA pathway to modulate memory, and corroborating that the effect transpires offline, during consolidation [16,17]. Despite no overall effect of tES side effects in the current study, we note that participants who received active ON-tDCS reported difficulty concentrating when this variable was taken separately.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The present study provides a replication of ON-tDCS having no direct effect on learning, but does have an effect on memory being observed on Day 7, further depicting active ON-tDCS' viability for upregulating the LC-NA pathway to modulate memory, and corroborating that the effect transpires offline, during consolidation [16,17]. Despite no overall effect of tES side effects in the current study, we note that participants who received active ON-tDCS reported difficulty concentrating when this variable was taken separately.…”
Section: Discussionsupporting
confidence: 71%
“…Alternatively, the present study incorporated a highly divergent study design regarding stimulation protocol, electrode location, and task type, to directly compare the behavioral effects generated by tDCS and tACS (an active and control for each: active tDCS, sham tDCS, 40 Hz tACS, 1 Hz tACS) when applied to the greater occipital nerve (ON) targeting the locus coeruleus (LC) while learning an associative memory task e replicating previous laboratory parameters strategic placement of electrodes on the left and right C2 nerve dermatomes [16,17] in an effort to polarize the regions [18]. In a series of experiments, we demonstrated ON-tDCS 0 viability to upregulate the locus coeruleus noradrenaline (LC-NA) pathway to increase LC and hippocampus connectivity and improve associative memory recall in young [17] and older [17] healthy participants.…”
Section: Introductionmentioning
confidence: 99%
“…Then, the Pathway 4 transfer function fitted to the post-stroke HbT data (shown in Figure 7C It is postulated that the Pathway 4 effects can be via norepinephrine [13] receptors on the pial arterial smooth muscle cells [14,15] that may be relevant at the onset (<150 sec after tDCS) of tDCS [9], [31]. Also, tES-evoked LC-NE activity can have therapeutic effects, e.g., cerebellar tDCS (ctDCS) electrode [34] may stimulate the ascending fibers of the occipital nerve [77]. Here, tDCS may stimulate the peripheral nerves [33] and the LC-NE system that can also lead to psychosensory pupil response as a dilation of the pupil.…”
Section: Grey-box Modeling Of Fnirs Of Tdcs Effectsa Chronic Stroke C...mentioning
confidence: 94%
“…Pathway 4 effects can postulated via norepinephrine [ 13 ] receptors on the pial arterial smooth muscle cells [ 14 , 15 ], which may be relevant at the onset (<150 s after tDCS) of tDCS [ 9 ]. Moreover, tES-evoked LC-NE activity via projections innervating the cerebral vasculature can have therapeutic effects, e.g., cerebellar tDCS (ctDCS) electrodes [ 33 ] may stimulate the ascending fibers of the occipital nerve [ 70 ]. Here, tES can be optimized to stimulate the peripheral nerves [ 32 ] and the LC-NE system.…”
Section: Grey-box Modeling Of Fnirs Of Tdcs’s Effects—a Chronic Strok...mentioning
confidence: 99%